The Environmental Aspect & Impacts for Industrial Sites: Methodological Framework and Evaluation - Adam Abdeljalil; Saffaj Nabil; Mamouni Rachid (Three E Science Institute, 2022)
Identifying linked environmental aspects and evaluating related impacts is a crucial requirement of any environmental management system for industrial facilities. Industrial sites should guarantee that a complete procedure for aspect identification and impact assessment is in place to fulfil international environmental protection and preservation requirements. The goal of this research was to develop a new procedure. Determine which environmental aspects of industrial sites (actions, products, and services) have or can have substantial consequences, and review and monitor their control regularly. Professional judgment will play an essential part in determining how to address significance in many cases, and this can be aided by collaboration with relevant stakeholders. The study's conclusion was creating a new environmental aspect evaluation system based on newly developed aspects and impacts rating matrix. Industrial sites could use this approach to identify and manage the environmental aspects of their operations.